Improved Cache trace driven attack on AES and CLEFIA - ZHAO Xin-jie1; GUO Shi-ze2; WANG Tao1; LIU Hui-ying1 (Tongxin xuebao)
An improved Cache trace attack on AES and CLEFIA was proposed by considering Cache miss trace informa-tion and S-box misalignment.Current trace driven attacks all assume that the S-box is perfectly aligned in Cache,and it’s impossible to recover the whole first round key of AES and CLEFIA under limited key searching space.However,the re-search demonstrates that the S-box is misaligned in Cache at most cases,by utilizing the Cache miss trace information of the cipher encryption,200 samples first round analysis and 50 samples last round analysis can reduce 128bit AES master key searching space to 216 and 1 respectively,80 samples first round analysis can reduce 128bit CLEFIA first round key searching space to 216,220 samples first three rounds analysis can reduce 128bit CLEFIA master key searching space to 216,all of the attacks above can be finished within 1 second.